DIGITAL MEDIA INTEGRATION AND STUDENT ENGAGEMENT IN INDONESIAN EFL CLASSROOMS - Lina Ardiyanti; Ima Isnaini Taufiqur Rohmah (Premise: Journal of English Education and Applied Linguistics, 2026)
Although digital media have been widely implemented in EFL learning, empirical evidence regarding their impact on students’ engagement across cognitive, emotional, and behavioral dimensions in Indonesian junior high school contexts remains limited. This study looks at how digital media are integrated into EFL classrooms and how it affects students' participation in an Indonesian junior high school. A mixed-method approach with an explanatory sequential design combined quantitative and qualitative data was used in the study. Participants were selected by purposive sampling. Data dikumpulkan melalui semi-structured interviews, observations di kelas, dan questionnaires. The quantitative data were analyzed using descriptive statistics, while the qualitative data were analyzed through reduction, display, and drawing conclusions. Among the three dimensions of engagement, the results showed that emotional engagement had the highest level, with a mean score of 3.87 on a five-point Likert scale. Engagement in behavioral and cognitive dimensions was the highest, followed by emotional engagement. Observational and interview data supported the findings. In summary, including digital media into EFL instruction effectively raises student involvement. According to this study, educators should make the most of digital media in order to develop more engaging and student-centered learning environments.